2013
DOI: 10.1007/s00429-013-0685-5
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II regulates actin rearrangement-related structural synaptic plasticity during conditioned taste aversion memory extinction

Abstract: Similar to memory formation, memory extinction is also a new learning process that requires synaptic plasticity. Actin rearrangement is fundamental for synaptic plasticity, however, whether actin rearrangement in the infralimbic cortex (IL) plays a role in memory extinction, as well as the mechanisms underlying it, remains unclear. Here, using a conditioned taste aversion (CTA) paradigm, we demonstrated increased synaptic density and actin rearrangement in the IL during the extinction of CTA. Targeted infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The IC is bidirectionally linked with the parvocellular portion of the ventroposteromedial thalamic nucleus (VPMpc), as well as the Central and Basolateral Amygdala (CeA and BLA), receiving and processing visceral and emotional information (Koh et al, 2003 ; Bermudez-Rattoni, 2004 ; Ferreira et al, 2005 ; Rosenblum, 2008 ; Lin and Reilly, 2012 ). More recent studies have suggested myosin II to regulate actin-related rearrangements in synaptic structure at the Infralimbic mPFC during CTAE (Bi et al, 2015 ). Further studies specific influence of such events on neurotransmission at the IC or indeed the extended taste during the different phases of taste learning would be particularly interesting.…”
Section: Synaptic Plasticity and Taste Learningmentioning
confidence: 99%
“…The IC is bidirectionally linked with the parvocellular portion of the ventroposteromedial thalamic nucleus (VPMpc), as well as the Central and Basolateral Amygdala (CeA and BLA), receiving and processing visceral and emotional information (Koh et al, 2003 ; Bermudez-Rattoni, 2004 ; Ferreira et al, 2005 ; Rosenblum, 2008 ; Lin and Reilly, 2012 ). More recent studies have suggested myosin II to regulate actin-related rearrangements in synaptic structure at the Infralimbic mPFC during CTAE (Bi et al, 2015 ). Further studies specific influence of such events on neurotransmission at the IC or indeed the extended taste during the different phases of taste learning would be particularly interesting.…”
Section: Synaptic Plasticity and Taste Learningmentioning
confidence: 99%
“…Memory-dependent structural plasticity that occurs during long-term potentiation (LTP) requires actin polymerization, the process of elongating filamentous actin (F-actin) by the addition of the monomeric globular form of actin (G-actin) (Lin et al 2005;Kramar et al 2006). Moreover, when actin depolymerizing agents are delivered to Area CA1 of the hippocampus (CA1), basolateral amygdala complex (lateral and basolateral amygdala; BLC), infralimbic region of the prefrontal cortex (IL, PFC) or nucleus accumbens (NAc) around the time of learning, memory formation fails (Fischer et al 2004;Mantzur et al 2009;Rex et al 2010;Gavin et al 2012;Bi et al 2015). Recently, we reported an unexpected and unique role for F-actin dynamics in the storage of memories associated with the highly addictive stimulant, methamphetamine (METH) (Young et al 2014(Young et al , 2015.…”
mentioning
confidence: 99%
“…More specifically, the structural plasticity of CTA memory extinction involves myosin II phosphorylation. Administration of myosin II ATPase inhibitors into the infralimbic cortex blocks the actin rearrangement mechanism and the subsequent CTA memory extinction [87]. These findings suggest that increased myosin II in the infralimbic cortex causes structural changes that modulate the appearance of new synapses through structural plasticity mechanisms during taste aversion memory extinction.…”
Section: Receptors Protein Expression Molecular Signalsmentioning
confidence: 77%
“…Actin rearrangement is a structural change mechanism that strengthens synapses. Actin rearrangement and increased synaptic density have been found in the infralimbic cortex during the extinction of CTA memory [87]. More specifically, the structural plasticity of CTA memory extinction involves myosin II phosphorylation.…”
Section: Receptors Protein Expression Molecular Signalsmentioning
confidence: 99%